Bullets, Tumours, and Justice: Forensic Pathology of Headshot Murders with Hidden Neoplasms in Indian Medico-Legal Law - Rajneesh Kumar; Gurminder Kaur; Ankit Anand; M. Shamima Parveen; Hrishikesh Manu (Indian Journal of Forensic Medicine and Pathology, 2025)
Background: Differentiation between traumatic injuries and pathological lesions continues to be one of the challenges in medico-legal practice, especially as intracranial tumours sometimes present features similar to the appearance of entrance or exit wounds caused by gun𿿿re. These misunderstandings maycompletely change the medico-legal scenario of the case, wrongly implicating homicide or concealment of crime. Objective: The article attempts to analyse the forensic challenges involved when post-mortem ballistic trauma to the skull is mistaken with tumour-related anomalies, and to evaluate how Indian medico-legal systems, including the Bharatiya Sakshya Adhiniyam, 2023, address the evidentiary implications of such intersections. Methods: A search was carried out on PubMed, Scopus, Web of Science, ResearchGate and Google Scholar between 1997 and 2024. The review gradually deliberates the information recycled from ongoing scienti𿿿c literature andlandmark case reports, legal-medico tenets emanating from the Indian setting, integrating the contribution of forensic pathology, forensic radiology and digital autopsy practices. Results: Results indicate that cranial tumours may radiologically or morphologically mimic a gunshot wound, posing a signi𿿿cant problemfor the investigator. Theintegration of neuropathology and forensic reconstruction, together with a supraspecialistic expert testimony, is necessary for removing doubts and enabling forensic admissibility of the evidence. Conclusion: An interdisciplinary approach is necessary to prevent miscarriage of justice in suspected headshot deaths with occult neoplasms by combining forensic medicine and law. More use of scienti𿿿c benchmarks, admissibility standards, andexpert interpretation may protect fair trial rights in cases of such complexity. Key Messages: Cranial tumours can be mistaken for gunshot wounds, and this can carry grave medico-legal implications with miscarriages of justice involving false convictions or acquittals. To obtain precision, it is necessary to cooperate with several disciplines, including forensic pathology, radiology and digital autopsy. De𿿿nitional clarity, stringent evidentiary standards and empirical validationarecritical to admissibility under Bharatiya Sakshya Adhiniyam, 2023, and call for a closer nexus between law and medicine to preclude unjust verdicts.